2021
DOI: 10.1057/s41599-020-00701-w
|View full text |Cite
|
Sign up to set email alerts
|

Toward effective government communication strategies in the era of COVID-19

Abstract: Several countries have successfully reduced their COVID-19 infection rate early, while others have been overwhelmed. The reasons for the differences are complex, but response efficacy has in part depended on the speed and scale of governmental intervention and how communities have received, perceived, and acted on the information provided by governments and other agencies. While there is no ‘one size fits all’ communications strategy to deliver information during a prolonged crisis, in this article, we draw on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
243
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(260 citation statements)
references
References 114 publications
7
243
0
10
Order By: Relevance
“…The results of the study are particularly relevant in the current conditions of macroeconomic instability, when the existing financial distribution systems are negatively affected due to the global COVID-19 pandemic. The optimal allocation of available financial resources among priority digital projects will contribute to a comprehensive increase in economic efficiency (Hyland-Wood et al 2021;Zimmerling and Chen 2021). Using the possibilities of building new approaches based on the developed tools will allow to rationalize the systematic use of digital innovations both in existing economic systems, and will provide the potential for creating completely new conceptual opportunities for newly created system entities (Khin and Ho 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the study are particularly relevant in the current conditions of macroeconomic instability, when the existing financial distribution systems are negatively affected due to the global COVID-19 pandemic. The optimal allocation of available financial resources among priority digital projects will contribute to a comprehensive increase in economic efficiency (Hyland-Wood et al 2021;Zimmerling and Chen 2021). Using the possibilities of building new approaches based on the developed tools will allow to rationalize the systematic use of digital innovations both in existing economic systems, and will provide the potential for creating completely new conceptual opportunities for newly created system entities (Khin and Ho 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In the scientific community, the issues of the formation of the digital space in the context of the global COVID-19 pandemic have become particularly acute. The current negative environment in the macroeconomic environment determines new trends in digital transformation, which was noted in previous articles (Hyland-Wood et al 2021;Zimmerling and Chen 2021). In 2020, major transformations of national economies took place, determining the accelerated dynamics of the transition to digital technologies, which is a serious opportunity to obtain new combinatorial effects.…”
Section: Literature Reviewmentioning
confidence: 92%
“…Government action and recovery-package incentives could have a significant long-term effect on global greenhouse gas levels (Le , with the potential to avoid 0.3°C of global warming by 2050 (Forster et al, 2020). During the COVID-19 pandemic, we have observed that frequent emphasis on the desired behaviour of citizens by governments increases the likelihood of behaviour change (Hyland-Wood et al, 2021). We can link our behavioural analysis using the COM-B model to potential interventions and policies identified in the integrative framework, the Behaviour Change Wheel (Michie et al, 2011).…”
Section: Policy Implicationsmentioning
confidence: 91%
“…Some countries have been shown to have quickly and successfully reduced infection rates, whilst some have been less responsive or effective ( Hyland-Wood et al, 2021 ). It has been observed that not all campaigns have resulted in notable increases in effective preventive health behaviors, with individuals responding differently to lockdown rules and social distancing measures.…”
Section: Introductionmentioning
confidence: 99%